Firm Size Distribution and its Changes Trend in Textile Manufacturing New Firms Using Non-Parametric Technique: 1997-2005 - Mohammad Ali Feizpour; Zohreh Ahmadi; Mehdi Emami Meibodi (پژوهشهای اقتصادی, 2014)
Entering firms into a business can be a sign of economic dynamism, but to what extent do they enter according to optimal size or converge to it? The answers are given in two approaches. In the first approach, a new- entrant enterprise adjusts its size by learning market and continues to its activity. In the second approach, the enterprise does not adjust its size and exits the market. In this regard, the study of size distribution of new enterprises in Iran’s textile industry is the main purpose of this research. We collect statistical data for new textile businesses during 1997-2005 from Statistical Center of Iran. We use nonparametric method and indicators of employment, output value and value-added for evaluation of the size distribution. The results indicate that the employment size distribution follows an active learning model and does not adapt itself with market conditions. Regarding output value and value-added, the textile businesses follow a passive learning model and converge to the Lognormal distribution. The inability of firms in convergence by employment and their ability in convergence by output and value added criteria are some signs of a rigid labor market in Iran. According to these findings, reconsidering the labor law in order to making it more flexible is essential.